2012
DOI: 10.3758/s13414-012-0328-6
|View full text |Cite|
|
Sign up to set email alerts
|

Base on balls for the Chapman strategy: Reassessing Brouwer, Brenner, and Smeets (2002)

Abstract: A true understanding of skilled behavior includes the identification of the information that underlies the perception–action cycle at work. Often, observers’ sensitivity to perceptual variables is established in laboratory-situated simulation-based psychophysical experiments. The observers’ sensitivity thus determined is then used to draw conclusions that will generalize the findings to natural behavior. Focusing on the example of running to catch fly balls, the present contribution takes the study of Brouwer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Because of drag and spin, fly balls do not follow parabolic trajectories (cf. [1] , [8] , [11] ), which implies that a sophisticated internal model of ball-flight dynamics would have to be postulated.…”
Section: Introductionmentioning
confidence: 99%
“…Because of drag and spin, fly balls do not follow parabolic trajectories (cf. [1] , [8] , [11] ), which implies that a sophisticated internal model of ball-flight dynamics would have to be postulated.…”
Section: Introductionmentioning
confidence: 99%
“…Given that parabolic trajectories move accelerated by terrestrial gravity, it is reasonable to consider humans’ ability to detect acceleration. Calderone and Kaiser ( 1989 ) proposed that acceleration in the visual system can be studied as the rate of change in speed divided by the average object speed in a two-stage process carried out in about 200 ms (Werkhoven et al, 1992 ; Zaal et al, 2012 ). This delay would mean that the observer would not continuously monitor the adequacy of their actions.…”
Section: Available Visual Informationmentioning
confidence: 99%
“…This delay would mean that the observer would not continuously monitor the adequacy of their actions. Furthermore, some studies found that it is necessary at least ~20% of the change in speed to detect acceleration (Gottsdanker et al, 1961 ; Werkhoven et al, 1992 ; Babler and Dannemiller, 1993 ; Brouwer et al, 2006 ; Zaal et al, 2012 ) indicating that humans are quite insensitive to changes in speed.…”
Section: Available Visual Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1a, the optical ball trajectory can be compared to that of an imaginary elevator rising from the home plate at a constant velocity and tilted by the amount that fielders run forward or backward (Babler & Dannemiller, 1993;McLeod & Dienes, 1993, 1996McLeod, Reed, & Dienes, 2003, 2006Michaels & Oudejans, 1992). Although some work examining acceleration discrimination has questioned OAC (Brouwer, Brenner, & Smeets, 2002;Zaal, Bongers, Pepping, & Bootsma, 2012), other Citation: Wang, W., McBeath, M. K., & Sugar, T. G. (2015). Optical angular constancy is maintained as a navigational control strategy when pursuing robots moving along complex pathways.…”
Section: Introductionmentioning
confidence: 99%